What are the preconditions for turnaround in failing states? - Chauvet, L; Collier, P (2007)
In this paper, we analyse the preconditions for sustained policy turnarounds in failing states. Our dependent variable is the probability of the commencement of a turnaround that eventually becomes both sustained and substantial. Among the explanatory variables we focus upon resource rents, education, and aid, distinguishing between finance and technical assistance. Overall, we find that these variables have significant and large effects on the duration of state failure. Appropriate donor intervention can radically shorten state failure, whereas additional finance, whether from aid or resource rents, has the opposite effect.